2020
DOI: 10.5812/asjsm.97122
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Training, in Combination with Listening Music, Changes Post-Exercise Cardiac Autonomic Function in Collegiate Overweight and Obese Individuals

Abstract: Background: Aerobic exercise and relaxing music induce parasympathetic activity over the heart. The combined effect of the two interventions was shown to reduce heart rate (HR), rate of perceived exertion (RPE), and anxiety levels. Objectives: The purpose of the study was to evaluate the effect of aerobic exercise along with music vs. only aerobic exercise, on the autonomic function of the heart during recovery in collegiate overweight and obese individuals. Methods: Thirty-two collegiate overweight and obese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Based on the findings of our study and supported by several previous studies, it is proven that music listened to during exercise has an effect on increasing metabolic ability to improve lipid profiles. Other findings also conclude that music listened to during exercise is a trigger for fat oxidation (Kim and Jee, 2020), an increase lipoprotein lipase activity (Tayagi et al, 2020), which can increase fat metabolism (Muscella et al, 2020) so that it can improve the lipid profile (Mirizio et al, 2020). Therefore, the exercise by listening to music is considered an oxidative exercise and contributes greatly to changes in fat metabolism (Kim and Jee, 2020).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on the findings of our study and supported by several previous studies, it is proven that music listened to during exercise has an effect on increasing metabolic ability to improve lipid profiles. Other findings also conclude that music listened to during exercise is a trigger for fat oxidation (Kim and Jee, 2020), an increase lipoprotein lipase activity (Tayagi et al, 2020), which can increase fat metabolism (Muscella et al, 2020) so that it can improve the lipid profile (Mirizio et al, 2020). Therefore, the exercise by listening to music is considered an oxidative exercise and contributes greatly to changes in fat metabolism (Kim and Jee, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Listening to music is also considered to reduce stress and relaxation, which is believed to improve metabolism and energy balance (Yamasaki et al, 2012). Previous research has shown that listening to music during exercise improves calm (Tayagi et al, 2020) and reduces cortisol secretion (Bigliassi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a significant contributor to an increase in heart disease, especially high blood pressure (Tayagi et al, 2020), myocardial infarction, (Almutawa et al, 2020) and coronary artery disease, (Machado et al, 2021), is also a major risk factor for death (Schroeder et al, 2019). Pharmacological approach (Zimmer et al, 2019) and an eating behavior change approach using diet in combination with medication (Shim & Kim, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity has been classified as a global disease [1] that severely impacts human health [2]. Obesity is a disease that has caused a high risk of complications [3], disability [4] and premature death [5], and morbidity and mortality in the global community [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies recommend that obesity prevention and control can be carried out using approaches, such as eating behavior transformation [11], reducing calorie intake diet, giving nutritional supplements consumption [6], lifestyle modification [12], changing environmental conditions [1], and also a pharmacological approach by providing drugs [13]. However, some of the methods recommended by previous studies are still considered ineffective [1] because they increase risk factors for complications and cause dependence [6], and require significant costs [2]. This approach is considered effective in the short term [8] because it can only reduce lean body weight, lower basal metabolism, and increase the risk of nutritional deficiencies [11].…”
Section: Introductionmentioning
confidence: 99%